A Study on the Oil Price Cointegration Dynamic Process: Evidence From the Shanghai Crude Oil Futures - Wang, Hongxia; Qiu, Shushu; Yick, Ho Yin; Dai, Yuhu (Frontiers in Environmental Science, 2022)
This work studies the integration process of the Shanghai crude oil futures market in pricing discovery mechanism of global crude oil markets by conducting cointegration analysis and lead–lag causality tests. Using the representative samples of several futures contracts covering different listing periods, we conclude a significant and gradual change of the relations between the Shanghai crude oil futures market and international benchmarks, from unidirectional Granger causality to bidirectional Granger causality. The cointegration relationships become stable after about 2 years’ market development. Moreover, the Shanghai crude oil futures market always leads domestic (Daqing) crude oil spot market since 2019. Our evidences support that it has the increasing influence on domestic crude oil market and international benchmarks.